Breast cancer incidence and mammography screening among resettlers in Germany - Kaucher, Simone; Becher, Heiko; Winkler, Volker (BMC public health, 2020)
European studies showed that women with a migration background are less likely to participate in mammography screenings than autochthonous women. However, the participation in the German mammography screening programme (MSP) among ethnic German migrants from countries of the former Soviet Union (called resettlers) is unclear so far. The aim of this study was to identify possible differences regarding MSP participation between resettlers from the FSU and the general German population.
Gesehen am 29.04.2020